OPPORTUNITIES FOR THE USE OF INFORMATION COMMUNICATION TECHNOLOGIES IN IMPROVING TEACHING METHODOLOGY IN MUSIC EDUCATION - Khamidovich, Akhrorov Khurshid (PT. Antis International Publisher, 2024)
This article describes and provides the necessary recommendations on the possibilities of using information communication technologies and its significant aspects in improving the teaching methodology in music education.